Analisis motivasi kerja dan disiplin kerja dampaknya terhadap kinerja pegawai ASN di kantor Dinas Tenaga Kerja dan Transmigrasi Provinsi Banten - Saleh, Muhammad; Bahits, Abdul; Muharommah, Meilani; Hidayat, Ardi; Fatoni, Malik (Management Journal and Economic Review, 2023)
Human resources have a major role in every company activity. As the main key, human resources will determine the success of the company's activities. The purpose of this study is to determine whether work motivation and work discipline partially and simultaneously affect employee perfomance at the office of manpower and transmigration in banten province. The research method used is a quantitative method. The populations in this study were 165 employees of the manpower and transmigration office of banten provinc. Based on the research, then researcher takes 20% of the existing population since the total population exceeds 100 i.e. 165 employees, means 165x20% = 33, therefore, the sample used in this study was 33 respondents. Therefore, researcher using questionnaire data that had been distributed to 20% of manpower and transmigration office of banten province employees, which were 33 respondents. Data analysis techniques used include classiacal assumption test, multiple linear regression test, T test and F test. The results of this study indicate that the indicators in this study are valid. The significance level of this study was 5% on the classical assumption test, the regression model was found to be normally distributed, free of multicollinearity and free of heteroscedasticity. Then the results of multiple regression obtained the equation Y= 6.426 + 0.582 X1 + 0.225 x2. The results of the study on the coefficients table obtained the results of the regression analysis of work motivation on employee performance, the tcount value was 3,946 and the ttable value was 2,045, so the tcount>ttable or 3,946>2,045, then Ho was rejected. While the work discipline obtained the results of regression analysis, the tcount value was 1,146,so the tcount < ttable or 1,146<2,045, then Ho be accepted.